2022
DOI: 10.1097/acm.0000000000004825
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Nature of Sexist Microaggressions Against Female Medical Students

Abstract: Sexism and microaggressions against females in the medical field are well-known occurrences. Although there is extensive research on the prevalence and effects of these microaggressions in residency and clinical practice, little research has been done at the level of medical students. 1,2 Medical schools are now composed of > 50% female students; however, gender discrepancies remain in clinical practice, and sexism during medical school training is likely a contributing factor. 3 The purpose of this study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…It may potentially signify the existence of societal pressure to downplay feminine attributes in the pursuit of success. [ 38 ]. In the context of veterinarians practicing in rural areas, it has been observed that the prevalence of sexist attitudes among certain farmers and colleagues constitutes a significant disadvantage [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may potentially signify the existence of societal pressure to downplay feminine attributes in the pursuit of success. [ 38 ]. In the context of veterinarians practicing in rural areas, it has been observed that the prevalence of sexist attitudes among certain farmers and colleagues constitutes a significant disadvantage [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we were interested in one form of covert discrimination in the U.S. military-gender microaggressions that target self-identified women (also referred to as sexist microaggressions; Cherry & Wilcox, 2021). Scholars have addressed gender microaggressions in a variety of contexts, such as undergraduate education (Gartner, 2021), medical school (Struble et al, 2022), and the workplace (Basford et al, 2014). With the notable exception of a technical report (Brown, 2011), gender microaggressions have not yet been addressed in the military.…”
Section: Gender Microaggressions: a Form Of Covert Discriminationmentioning
confidence: 99%